A passive and conservative technique for the retrieval of foreign bodies in lower second premolar - Abdul Rahaman Jarallah Al Ghamdi (Wolters Kluwer Medknow Publications, 2017)
Metallic obstructions in the root canal space render its removal or negotiation by-passing one of the most challenging procedures encountered in the endodontic retreatment which may jeopardize the tooth structures, several procedures had been advocated. In this case, due to limited available equipment negotiating these obstructions by passive and conservative approach had been implemented.